1932 La. Acts 337-38 - (:unkn) unknown (My University, 1932)
No. 79,§ 1-2: Prohibited selling, loaning, giving, purchasing, possession, carrying, or transporting a machine gun.
Keywords: MACHINE GUN RESTRICTION